Uveitis and Papillitis in the Setting of Dabrafenib and Trametinib Therapy for Metastatic Melanoma: A Case Report. (19th May 2018) - Lim, Jennifer; Lomax, Anna J.; McNeil, Catriona; Harrisberg, Brian
ABSTRACT: Purpose : To report the diagnosis of acute VKH-like syndrome as a complication from dabrafenib (a serine/threonine inhibitor of BRAF V600 ) and trametinib (a MEK inhibitor). In combination, these targeted agents have been shown to prolong overall survival and progression free survival in BRAF mutant metastatic melanoma. Methods : Retrospective medical chart review including radiologic and ophthalmologic investigations. Results : A patient with metastatic melanoma being treated with dabrafenib and trametinib for 2 months presented with 1 week of visual blurring. He had developed bilateral optic disc swelling and uveitis that responded to pulsed steroid therapy. Conclusions : VKH-like syndrome is a rare but serious complication of targeted therapy that should be considered when evaluating a patient with visual disturbances on dabrafenib and trametinib therapy.